2018
DOI: 10.3389/fneur.2018.00633
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Celecoxib on Early Postoperative Cognitive Dysfunction in Geriatric Patients

Abstract: Objective: Inflammation plays a key role in the etiology and pathology of postoperative cognitive dysfunction (POCD). Cyclooxygenase (COX)-2 inhibitor celecoxib is used for the treatment of acute pain due to its potent anti-inflammatory and analgesic effects. Herein, we evaluated the effects of celecoxib on POCD in geriatric patients.Methods: A total of 178 geriatric patients undergoing total knee arthroplasty were randomly divided into two groups and treated with celecoxib (group C) or placebo (group P). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 29 publications
(32 reference statements)
0
15
0
1
Order By: Relevance
“…of 165 patients after TKA suggested that preoperative administration of etoricoxib 120 mg orally was superior to postoperative administration of the same dose in terms of its morphine‐sparing effect during the first postoperative 48 h, without difference in the incidence of side effects. Apart from analgesia, celecoxib and parecoxib could also decrease early postoperative cognitive dysfunction incidence after TKA in elderly patients. At present, COX‐2 inhibitors are usually added to multimodal analgesia to reduce the consumption of opioids, without serious complications.…”
Section: Preoperative Analgesic Regimensmentioning
confidence: 99%
“…of 165 patients after TKA suggested that preoperative administration of etoricoxib 120 mg orally was superior to postoperative administration of the same dose in terms of its morphine‐sparing effect during the first postoperative 48 h, without difference in the incidence of side effects. Apart from analgesia, celecoxib and parecoxib could also decrease early postoperative cognitive dysfunction incidence after TKA in elderly patients. At present, COX‐2 inhibitors are usually added to multimodal analgesia to reduce the consumption of opioids, without serious complications.…”
Section: Preoperative Analgesic Regimensmentioning
confidence: 99%
“…89,90 Blockage of either tumor necrosis factor α or interleukin 6 using antibodies effectively reduced rodent postoperative cognitive dysfunction, but also delayed wound healing. 79,82 More conventional antiinflammatory drugs (dexamethasone and cyclooxygenase-2 inhibitors) given before, during, or after the procedure have yielded variable results, [91][92][93][94][95] a result that has shifted attention to innate processes that actively turn off or resolve inflammation. Initial studies of mice with the tibial fracture model show promising results with proresolution strategies, such as resolvin-D1 and maresin-1, 96,97 as well as bioelectronic approaches, such as electrical stimulation of the vagus nerve.…”
Section: Rodents (Mice and Rats)mentioning
confidence: 99%
“…In a trial of 134 elderly patients, parecoxib was shown to decrease pro-inflammatory markers and POCD incidence (as assessed using a neurocognitive battery) compared to placebo at 1 week, but not 3 months following surgery (152), although this negative result was largely due to improved cognitive performance in the placebo group. Similarly, a trial of 178 elderly patients showed that celecoxib reduced pro-inflammatory markers and POCD (determined by reduction in performance of ≥2 of 5 cognitive tests) at 1 week following surgery compared to placebo (153). There are no ongoing registered clinical trials testing the use of NSAIDs or selective COX-2 inhibitors in POCD.…”
Section: Proposed Treatments For Pocdmentioning
confidence: 99%
“…Indeed, rodent models have shown that the COX-2 inhibitor parecoxib is capable of downregulating IL-1 β and TNFα expression (168); furthermore, meloxicam, a non-steroidal anti-inflammatory drug (NSAID) with relative selectivity for COX-2 has been shown to decrease short-term deficits in recognition memory following surgery (169). So far, two human trials have evaluated the efficacy of COX-2 inhibition on POCD, both in geriatric patients undergoing total knee arthroplasty (152, 153). In a trial of 134 elderly patients, parecoxib was shown to decrease pro-inflammatory markers and POCD incidence (as assessed using a neurocognitive battery) compared to placebo at 1 week, but not 3 months following surgery (152), although this negative result was largely due to improved cognitive performance in the placebo group.…”
Section: Proposed Treatments For Pocdmentioning
confidence: 99%